1993
DOI: 10.1530/acta.0.1280339
|View full text |Cite
|
Sign up to set email alerts
|

Plasma corticotropin-releasing hormone, β-endorphin and cortisol inter-relationships during human pregnancy

Abstract: To investigate the dynamic relationships among corticotropin-releasing hormone (CRH), \g=b\-endorphin (\g=b\EP), cortisol and obstetric events during pregnancy, blood samples were collected from 193 women at 28 weeks, 38 weeks, during labour and on the second postnatal day. Cord blood at delivery was also obtained. We found that: (1) Maternal plasma CRH, \g=b\EPand cortisol rose from 28 to 38 weeks. (2) During the third trimester maternal plasma CRH and \g=b\EP were correlated (r=0.30, p<0.001). (3) During lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 15 publications
(34 reference statements)
3
37
0
Order By: Relevance
“…Additionally, placental CRH could be ineffective because the CRH-binding protein counteracts the secretory action of CRH on maternal and placental ACTH as well (14). It has been shown also that plasma CRH and ACTH levels both rise during the latter half of pregnancy, supporting the hypothesis that placental CRH stimulates maternal corticotrophs (15,16). On the other hand discrepancies occur between CRH and ACTH levels during pregnancy, because plasma ACTH remains within the range of nonpregnant subjects, despite extremely elevated maternal CRH concentrations (17).…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, placental CRH could be ineffective because the CRH-binding protein counteracts the secretory action of CRH on maternal and placental ACTH as well (14). It has been shown also that plasma CRH and ACTH levels both rise during the latter half of pregnancy, supporting the hypothesis that placental CRH stimulates maternal corticotrophs (15,16). On the other hand discrepancies occur between CRH and ACTH levels during pregnancy, because plasma ACTH remains within the range of nonpregnant subjects, despite extremely elevated maternal CRH concentrations (17).…”
Section: Discussionmentioning
confidence: 93%
“…Cortisol and insulin concentrations, which increase during pregnancy (Kuhl, 1991;Chan et al, 1993), may also stimulate the production of leptin from the adipocytes. The possibility, however, exists that leptin is produced by the placenta, since there is evidence that human placenta expresses ob gene (Luoh et al, 1997;Masuzaki et al, 1997;Senaris et al, 1997).…”
Section: Pregnancymentioning
confidence: 99%
“…Chan et al [17] found no correlation between maternal plasma CRH and cortisol during delivery or the duration of labor, but in contrast, Smith et al [18] did report a correlation between maternal plasma CRH and cortisol during labor. Wolfe et al [8] were able to show an association between CRH levels, gestational age and weight gain during pregnancy, but with no other obstetric variable.…”
Section: Introductionmentioning
confidence: 96%